English Translation Techniques - Deng, Fei, contributor; Zhang, Li, contributor; Wen, Xu, contributor; Asmah Omar, contributor; Wang, Fang, contributor; Alhabib, Samia, contributor; Feder, Gene, contributor; Horwood, Jeremy, contributor; Saz, Oscar, contributor; Lin, Yibin, contributor; Eskenazi, Maxine, contributor; Alireza Mahmoudi, contributor; et al. (United Kingdom : Koros Press Limited, 2015)
Includes bibliographical references :p.267